Effect of channel spacing on the signal quality for a bi-directional TWDM PON - Ur Rehman, Shahid (Penerbit UTM Press, 2016)
As the demand for broadband services increase coupled with the introduction of new services like online interactive gaming, high definition video TV, video on demand etc., the ability to support higher data rates and efficient utilization of the deployed network is necessary. This largely depends on the capacity and quality of the access networks. Currently deployed Passive Optical Networks (PON) like GPON and EPON will not be able to meet the growing demand in the future. Although both of these PONs have evolved to their respective 10G versions called XG-PON and 10G-EPON, they will eventually reach the limit of their capacity. This has paved the way for the next evolution of PON named as Next Generation PON Stage-2 (NG-PON2). NG-PON2 has the advantage of a much larger bandwidth and scalability by using a combination of Time and Wavelength Division Multiplexing known as TWDM PON. In this paper we have investigated the effect of varying channel spacing (50GHz, 100GHz and 200GHz) on the quality of a Bi-directional TWDM PON signal. The best results were obtained with the widest channel spacing of 200GHz (1.6nm).